2006
DOI: 10.1016/j.jacc.2005.07.070
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Radiofrequency Ablation Lesions With Gadolinium-Enhanced Cardiovascular Magnetic Resonance Imaging

Abstract: Radiofrequency ablation can be evaluated accurately by using gadolinium-enhanced MRI, which may allow the noninvasive assessment of procedural success. The dissimilar wash-in and wash-out kinetics compared with myocardial infarction suggest a different pathophysiological process with complete loss of microvasculature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
145
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(159 citation statements)
references
References 29 publications
9
145
0
1
Order By: Relevance
“…5A-C), which virtually did not differ from that formed after occlusion infarction. Interestingly an MRI study of the progression of injury evoked by radiofrequency ablation [60] showed patterns similar to that observed for cryoinjury.…”
Section: Mechanism Of Cryoinjurymentioning
confidence: 59%
“…5A-C), which virtually did not differ from that formed after occlusion infarction. Interestingly an MRI study of the progression of injury evoked by radiofrequency ablation [60] showed patterns similar to that observed for cryoinjury.…”
Section: Mechanism Of Cryoinjurymentioning
confidence: 59%
“…6 Radiofrequency ablation lesions may be visualized after ablation to assess the extent of myocardial injury. 7,8 Furthermore, MRIs acquired at the time of the procedure provide accurate representations of the true anatomy and are, by definition, registered without the use of any fiducial structures because the images and navigational data are acquired in the same coordinate frame. High-speed MRI has already been successfully used to navigate catheters through the body and cardiac chambers and has been shown to be accurate enough to perform transseptal puncture and stenting of aortic coarctation.…”
Section: Clinical Perspective P 862mentioning
confidence: 99%
“…Further, EAM is associated with a risk of incorrectly identify areas of low voltage due to poor contact. 35,36 Delayed enhancement MRI (DE-MRI) and multidetector CT (MDCT) imaging have emerged as valuable adjunctive techniques that may overcome some of the limitations of using EAM in isolation. As is the case in AF patients, DE-MRI and MDCT images can be integrated with EAM maps.…”
Section: Advances In Imaging Techniques For Vt Ablationmentioning
confidence: 99%